A comparative study on the development of Taijiquan and Xinxinquan-- Based on CNKI literature analysis (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: Go abroad in order to promote more Chinese excellent traditional culture, is a world-class intangible cultural heritage projects taijiquan and state-level non-material cultural heritage six-mergence boxing in the similarities and differences between inheritance development, explore the taijiquan in the heart, which can be used for reference in the development of test analysis is applied to the successful experience of taijiquan propagation Xinyiquan and other traditional boxing feasibility. To provide "Taiji Solution" for the spread and development of traditional martial arts. Methods: Using the literature method and comparative research method, 7,467 journal papers on the theme of "Taijiquan" and 375 journal papers on the theme of "Xinxinquan" were retrieved from CNKI from 2001 to 2021 for quantitative visual comparative analysis. Results: First, Taijiquan has formed a more mature theoretical research system. First of all, in terms of the number of studies, compared with Xinyiquan, the number of studies related to Taijiquan has steadily increased year by year. According to the quantitative analysis of CNKI, the number of studies related to Taijiquan has been rising rapidly in a step-type way since 2001, and in the past decade, the total number of papers published in journals has reached more than 400. However, the research process of Xinyiquan is relatively slow, and the number of papers published on related topics in the peak period of research only keeps at 30 to 40 papers per year, and the research heat of related topics only lasts for two years and then begins to decline. Secondly, in terms of research direction, Taijiquan integrates its skills and techniques into medical practice. Taijiquan has not only been widely used in clinical medicine, special medicine, neurology, preventive medicine and hygiene and other kinds of medicine, but also in the prevention and treatment of cardiovascular system diseases, respiratory diseases, endocrine gland and systemic diseases and other diseases to obtain good practical effects. However, Xinyiquan mostly focuses on the researches related to martial arts, techniques and other fields, and lacks the combination with other fields such as traditional Chinese medicine. Therefore, the progress of relevant theoretical research is slow. Second, Taijiquan has shaped a more mature practice mode. First of all, on the cultural value shape, as the first batch of national intangible cultural heritage project, Taijiquan people attach great importance to its unique theoretic culture transmission, carry forward the concept of Taijiquan "cultivate one's morality raises a gender", actively response to the "national fitness", "sports power" and a series of policies, become the important path of national fitness culture. It was inscribed on the Representative List of the Intangible Cultural Heritage of Humanity by UNESCO in 2020. Secondly, in terms of commercial brand promotion, a number of Taijiquan inheritor have shaped "Taijiquan cultural brand" with the help of modern business operation mode, and formed the city name card of Taijiquan represented by Chenjiagou. At the same time, the brand image of "self-cultivation and nourishment" of Taijiquan should be vigorously shaped, and the commercialization problems in the development process of Taijiquan should be adjusted by the market mechanism. Moreover, in the expansion of communication channels, modern information technology is used to carry out multi-channel transmission in the development of Taijiquan communication. With the help of the Internet, the Internet of Things and other online communication, VR promotion and other diversified communication, not only enriches the transmission path of Taijiquan, but also greatly improves the transmission efficiency of Taijiquan with vivid and interesting forms of communication. And mind Xinyiquan fully absorb and draw lessons from the creation and development of the essence of Chinese traditional culture, formed the dominated by liuhe thoughts, single simplified combat as the core, the offensive and defensive changes as the essence, outside the spirit of god, to practice within the physique as the basis of systematic theory and technology system, contain the recuperate stock system thought. It contains infinite potential cultural value and commercial application mode, but its own development mode is still not mature, and there are problems such as communication intensity, communication breadth and communication validity, etc. It is urgent to learn from the successful experience of Taijiquan and explore a unique route suitable for the development of Xinyiquan. Conclusion: Traditional Wushu contains the brand of Chinese civilization in the process of theoretical research and practical dissemination. As one of the four traditional Chinese quanshu, Taijiquan and Xinhuquan have fully absorbed the essence of Chinese traditional culture, become the classics of traditional Wushu and have been listed in the list of national intangible cultural heritage. However, under the background of globalization and informationization, the development of many kinds of traditional wushu represented by Xinyiquan has been limited to a certain extent, and its theoretical research and practice spread process is slow, at the same time, it faces the embarrassing situation of weak spread and no successor. Compared with Xinyiquan, Taijiquan is well adapted to the disease and has been integrated into the modernization process, and has formed a relatively mature theoretical research system and practical operation mode. First of all, in terms of theoretical research, Taijiquan techniques and techniques integrate traditional Chinese medicine theory, give full play to the value and effect of traditional Chinese thought, and apply Taijiquan thought and Taijiquan techniques in clinical research of traditional Chinese medicine, which not only expands the theoretical effect of Taijiquan, but also enriches the operation and application of traditional Chinese medicine. Secondly, in terms of practice and operation, Taijiquan fully demonstrates the Chinese philosophy and shapes the unique values with self-cultivation as the theme. It has formed a unique brand culture. With the help of the Internet + wave, it carries out the multi-channel communication mode, constructs a relatively perfect development system and creates the "Road of Taijiquan", which not only provides a reference for the development of Xinyiquan, but also provides a model for the system construction of other traditional martial arts.